To simplify the expression \( \frac{7}{8 + \sqrt{3}} \) and rationalize the denominator, follow these steps:
- Multiply both the numerator and the denominator by the conjugate of the denominator \( 8 - \sqrt{3} \):
\[ \frac{7}{8 + \sqrt{3}} \cdot \frac{8 - \sqrt{3}}{8 - \sqrt{3}} = \frac{7(8 - \sqrt{3})}{(8 + \sqrt{3})(8 - \sqrt{3})} \]
- Calculate the denominator using the difference of squares formula:
\[ (8 + \sqrt{3})(8 - \sqrt{3}) = 8^2 - (\sqrt{3})^2 = 64 - 3 = 61 \]
- Calculate the numerator:
\[ 7(8 - \sqrt{3}) = 56 - 7\sqrt{3} \]
- Combine everything:
\[ \frac{56 - 7\sqrt{3}}{61} \]
So, the simplified and rationalized form of the expression is:
\[ \frac{56 - 7\sqrt{3}}{61} \]